2013
DOI: 10.1038/eye.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

Serum YKL-40 levels as a novel marker of inflammation and endothelial dysfunction in patients with pseudoexfoliation syndrome

Abstract: Purpose To evaluate serum levels of YKL-40 in patients with pseudoexfoliation syndrome (PEX) in comparison with those of age-and sex-matched healthy subjects. Methods Forty patients with PEX (PEX group) and 40 age-and sex-matched control subjects (control group) were enrolled in the study. An enzyme immunoassay method using the commercially available test MicroVue YKL-40 was used to measure serum YKL-40 concentration. Systolic and diastolic blood pressures, serum levels of high sensitivity C-reactive protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Additional evidence is provided by the finding of increased levels of activity of antioxidants like superoxide dismutases, aldehyde dehydrogenase 1, and microsomal GST1 in anterior lens epithelium of eyes with PEX, suggesting that diseased tissue appears to respond to oxidative stress [45]. Elevated serum levels of YKL-40, which is a proinflammatory protein used as novel marker of inflammation and endothelial dysfunction, have also been recently reported in patients with PEX compared to age-matched controls [46].…”
Section: Key Pointsmentioning
confidence: 92%
“…Additional evidence is provided by the finding of increased levels of activity of antioxidants like superoxide dismutases, aldehyde dehydrogenase 1, and microsomal GST1 in anterior lens epithelium of eyes with PEX, suggesting that diseased tissue appears to respond to oxidative stress [45]. Elevated serum levels of YKL-40, which is a proinflammatory protein used as novel marker of inflammation and endothelial dysfunction, have also been recently reported in patients with PEX compared to age-matched controls [46].…”
Section: Key Pointsmentioning
confidence: 92%
“…[15][16][17] The relationship between NLR and diabetic retinopathy was shown. 11 The assessment of NLR in patients with AMD was studied by Ilhan N et al 17 In their study, patients with AMD have higher NLR compared with controls and NLR correlates with age and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PEXS and serum YKL-40, a proinflammatory protein that has been demonstrated to have a role in the pathogenesis of endothelial dysfunction was shown. 11 Proinflammatory cytokines in eyes with early and late stages of PEX syndrome/glaucoma were studied. 12 The authors support a role for a stressinduced, spatially, and temporally restricted subclinical inflammation in the onset of the fibrotic matrix process characteristic of PEXS/PEXG.…”
Section: Discussionmentioning
confidence: 99%
“…Either serum or aqueous humor concentration of asymmetric dimethyl arginine was found to be significantly higher in patients with PES compared with healthy controls, which implies that endothelial dysfunction plays a role in this particular systemic disease. Similarly, Turkyilmaz et al 24 have shown a relationship between PES and elevated serum levels of YKL-40 (chitinase-3-like protein 1), which has a role in endothelial dysfunction and inflammation. To date, elevated serum levels of several other molecules that have definitive roles in inflammatory processes (eg, cardiovascular and cerebrovascular disease, endothelial dysfunction), including high-sensitivity C-reactive protein, 25 tumor necrosis factora, 25 antiphospholipid antibody, 26 a 1-antitrypsin, 27 homocysteine, 28 and hydroxyproline 29 have been studied in the serum of patients with PES.…”
Section: Discussionmentioning
confidence: 95%